IMPACT OF VARYING AMOUNTS OF PEANUT (Arachis hypogaea) MEAL ON RAINBOW TROUT (Oncorhynchus mykiss) DIETS INSTEAD OF SOYBEAN MEAL ON THE ELEMENTAL COMPOSITION AND BIOMAGNIFICATION FACTORS IN FILLETS - ÖZTÜRK, DİLARA KAYA; KARAYÜCEL, İsmhan; Dernekbaşi, Seval; Özdemir, Keriman yürüten (Science Journal of University of Zakho, 2025)
In this study, the effects of using different ratios of peanut meal (PNM) instead of soybean meal in rainbow trout (Oncorhynchus mykiss) diet on elemental composition and biomagnification factor (BMF) were evaluated for 12 weeks. Three experimental diets containing 50% (PNM50), 75% (PNM75), and 100% (PNM100) peanut meal were prepared. In the study, two control groups were fed a commercial feed (CF) and a diet containing 0% PNM (C), respectively. The CF had the greatest Ca/P ratio and the highest Se, Ca, and P levels, and these values were also significantly different from the other experimental diets. The PNM75 diet had significantly higher Mn and Cu values (p
Keywords: Biomagnification factor; element composition; Oncorhynchus mykiss; peanut meal